Most Frequent Esophageal Foreign Bodies Ingested by Children - Altay, Derya; Arslan, Duran (My University, 2019)
Objective: The presence of a foreign body in the esophagus represents one of the gastroenterological emergencies. In thisstudy, we aimed to evaluate retrospectively foreign bodies attached to the esophagus.Materials and Methods: The files of pediatric patients admitted to the university hospital due to ingestion of foreign bodiesbetween January 2018 and January 2019 were examined retrospectively, and those attached to the esophagus wereevaluated.Results: A total of 215 pediatric patients were admitted with the complaint of foreign bodies ingestion, and 63 (29.3%) ofthem had foreign bodies impacted in the esophagus. The mean age of the 63 patients (55.6% males) was 4.8±3.9 years.The mean age of 152 cases (58% males) was 5.3±3.8 years. Of the cases with foreign bodies impacted in the esophagus,10% were Syrian refugees. Most of the foreign bodies removed from the esophagus endoscopically were coins, which werefrequently attached to the upper esophageal sphincter. In the remaining patients, the foreign bodies (mostly coins) passthrough the gastrointestinal tract without any problems.Conclusion: Endoscopy is an important method in the treatment of esophageal foreign bodies. An early intervention isimportant in patients who ingested a button battery. However, adolescents who have food impacted in the esophagus shouldbe evaluated earlier in terms of eosinophilic esophagitis.
Keywords: Gastroenteroloji ve Hepatoloji